Constituents of a Global Mindset: An Empirical Study with Japanese Managers - Ananthram, Subra; Grainger, Richard; Tominaga, H. (Southern Japan Seminar and Asian Studies at Florida International University, 2014)
Based on government-inspired economic development in the Meiji Era and again in the aftermath of the Pacific War, Japan had quickly established itself as a major contributor to global business. In the case of the Meiji Era expansion, the dramatic advances have commonly been interpreted as resulting from the herculean efforts of a special group, namely ex-samurai leaders acting as agents of the administration, and in the post-war reconstruction period, a larger societal sub-group, Japanese “salary men,” functioned as the agents of change. Each of these groups has been associated with special qualities, in particular a single-minded dedication to hard work for nation and company. With this historical background in mind, and coming after a period of some two decades of economic decline, the current empirical research study was conducted in order to map out an appropriate global mindset “profile” for Japanese business managers engaged in contemporary global business. After establishing the constructs by which “global mindset intensity” could be assessed, a questionnaire survey (n=71) and subsequent in-depth interviews (n=11) were undertaken with Japanese international managers in western Japan. Based on the findings from this pluralist methodology, the researchers have suggested that the ideal corporate role model of Japan’s post-war reconstruction and growth period, the “salary man,” was now effectively redundant, and that the currently accepted ideal profile for Japanese international businessmen was more worldly and individualistic, with expertise and “global mindset intensity” drawn from personalized international business experience, reminiscent of established Western business ideals.